OCaMIR-A Noninvasive, Diagnostic Signature for Early-Stage Ovarian Cancer: A Multi-cohort Retrospective and Prospective Study - Kandimalla, Raju; Wang, Wei; Yu, Fan; Zhou, Nianxin; Gao, Feng; Spillman, Monique; Moukova, Lucie; Slaby, Ondrej; Salhia, Bodour; Zhou, Shengtao; Wang, Xin; Goel, Ajay (Clinical cancer research, 2021)
PURPOSE: Due to the lack of effective screening approaches and early detection biomarkers, ovarian cancer has the highest mortality rates among gynecologic cancers. Herein, we undertook a systematic biomarker discovery and validation approach to identify microRNA (miRNA) biomarkers for the early detection of ovarian cancer. EXPERIMENTAL DESIGN: During the discovery phase, we performed small RNA sequencing in stage I high-grade serous ovarian cancer (n = 31), which was subsequently validated in multiple, independent data sets (TCGA, n = 543; GSE65819, n = 87). Subsequently, we performed multivariate logistic regression-based training in a serum data set (GSE106817, n = 640), followed by its independent validation in three retrospective data sets (GSE31568, n = 85; GSE113486, n = 140; Czech Republic cohort, n = 192) and one prospective serum cohort (n = 95). In addition, we evaluated the specificity of OCaMIR, by comparing its performance in several other cancers (GSE31568 cohort, n = 369). RESULTS: The OCaMIR demonstrated a robust diagnostic accuracy in the stage I high-grade serous ovarian cancer patients in the discovery cohort (AUC = 0.99), which was consistently reproducible in both stage I (AUC = 0.96) and all stage patients (AUC = 0.89) in the TCGA cohort. Logistic regression-based training and validation of OCaMIR achieved AUC values of 0.89 (GSE106817), 0.85 (GSE31568), 0.86 (GSE113486), and 0.82 (Czech Republic cohort) in the retrospective serum validation cohorts, as well as prospective validation cohort (AUC = 0.92). More importantly, OCaMIR demonstrated a significantly superior diagnostic performance compared with CA125 levels, even in stage I patients, and was more cost-effective, highlighting its potential role for screening and early detection of ovarian cancer. CONCLUSIONS: Small RNA sequencing identified a robust noninvasive miRNA signature for early-stage serous ovarian cancer detection.
Keywords: MicroRNAs; kohortové studie; retrospektivní studie; Cohort Studies; Neoplasm Grading; Ovarian Neoplasms; Neoplasm Staging; mikro RNA; Adult; Aged; dospělí; Prospective Studies; senioři; nádory vaječníků; senioři nad 80 let; Cystadenocarcinoma, Serous; serózní cystadenokarcinom; lidé; ženské pohlaví; Biomarkers, Tumor; stupeň nádoru; Humans; Early Detection of Cancer; Aged, 80 and over; Retrospective Studies; Female; lidé středního věku; staging nádorů; nádorové biomarkery; časná detekce nádoru; Middle Aged; prospektivní studie